Respostas
respondido por:
4
Oi
a)4x-6=22
4x=22+6
4x=28
x=28/4
x=7
b)9-x=2x
2x+x=9
3x=9
x=9/3
x=3
c)8+4x=6x-4
6x-4x=8+4
2x=12
x=12/2
x=6
d)3x+1=x+9
3x-x=9-1
2x=8
x=8/2
x=4
e)4x-11=7-2x
4x+2x=7+11
6x=18
x=18/6
x=3
f)3x+1=5+x
3x-x=5-1
2x=4
x=4/2
x=2
a)4x-6=22
4x=22+6
4x=28
x=28/4
x=7
b)9-x=2x
2x+x=9
3x=9
x=9/3
x=3
c)8+4x=6x-4
6x-4x=8+4
2x=12
x=12/2
x=6
d)3x+1=x+9
3x-x=9-1
2x=8
x=8/2
x=4
e)4x-11=7-2x
4x+2x=7+11
6x=18
x=18/6
x=3
f)3x+1=5+x
3x-x=5-1
2x=4
x=4/2
x=2
StormPlus:
Grato João
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás